2014
DOI: 10.3892/mmr.2014.2647
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus and expression of osteopontin in cervical cancer specimens

Abstract: Abstract. To understand human papillomavirus (HPV) and expression of osteopontin (OPN) in cervical diseased tissues, HPV infection was detected in paraffin-embedded specimens of cervical lesions from 90 patients with cervical cancer. Three polymerase chain reaction (PCR) techniques were used to determine the detectable rate of HPV infection. Expression of HPV OPN protein was detected using immunohistochemical methods. When a pairwise comparison was made among the three PCR methods, χ 2 analysis indicated P>0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…23,24 Further, the 5-year overall rate of advanced-stage patient survival has remained below 40%. 23,24 Further, the 5-year overall rate of advanced-stage patient survival has remained below 40%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Further, the 5-year overall rate of advanced-stage patient survival has remained below 40%. 23,24 Further, the 5-year overall rate of advanced-stage patient survival has remained below 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical carcinoma is a malignant solid tumor, and it is also one of the main causes of both morbidity and mortality in women, with China having approximately one-third of the incidence and mortality in the world based on statistical data. 23,24 Further, the 5-year overall rate of advanced-stage patient survival has remained below 40%. 25 Thus, it is paramount to explore more effective prognostic evaluations as well as to identify improved therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, OPN was found to act as an oncogene during tumorigenesis of CC ( Cho et al, 2008 ; Bao et al, 2015 ; Xu et al, 2019 ). High expression of OPN was correlated with a higher FIGO stage, larger tumor size, lymph node metastasis, HPV infection, cisplatin resistance and shorter survival ( Bao et al, 2015 ; Huang et al, 2015 ; Xu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 85%
“…In previous reports, OPN was found to act as an oncogene during tumorigenesis of CC ( Cho et al, 2008 ; Bao et al, 2015 ; Xu et al, 2019 ). High expression of OPN was correlated with a higher FIGO stage, larger tumor size, lymph node metastasis, HPV infection, cisplatin resistance and shorter survival ( Bao et al, 2015 ; Huang et al, 2015 ; Xu et al, 2019 ). Nonetheless, the immunological and metabolic features of OPN in CC have not been sufficiently investigated, and clinical characteristic analysis using gene datasets from multiple databases has never been performed.…”
Section: Introductionmentioning
confidence: 85%
“…The experimental expression of the E6 and E7 proteins of HPV-16 increased the expression of VEGF/interleukin-8 and decreased that of TSP-1 in keratinocytes ( Table 1 ) [ 96 , 97 , 98 ], suggesting that those HPV proteins are involved in angiogenesis. Bao et al reported that OPN was highly detected in HPV-positive patients with cervical cancer, suggesting that OPN could be involved in the HPV-associated progression of cervical cancer [ 99 ]. However, that study did not describe any relationship between the HPV proteins and the enhanced OPN expression in HPV-positive lesions.…”
Section: The Involvement Of Matricellular Proteins In the Tumorigementioning
confidence: 99%